INTERNALISASI NILAINILAI ISLAM DALAM MEMINIMALKAN INFEKSI SOIL TRANSMITTED HELMINTH PADA PETANI KUBIS MELALUI PENDIDIKAN BERBASIS MASYARAKAT - Saputro, Budiyono (Madania: Jurnal Kajian Keislaman, 2015)
Internalization of Islamic Values in Minimizing Soil transmitted Helmints Infection in Cabbage Farmersthrough Community-Based Education. Cabbage farmers in conducting activities in the field is always related tosoil and manure. The problem that caused is the presence of intestinal helminth infections Soil TransmittedHelmints (STH). STH is intestinal nematodes. infection of the life cycle through the land. STH came from thephylum Nemathelminths namely A. lumbricoides, T. trichiura, A. duodenale, N. americanus, S. Stercoralis.This is a qualitative research methode. Based on the results of this research concluded that: a) the conditionof cabbage farmers in the village a model Kaponan District of Pakis Magelang are particularly vulnerable tothe dangers of infection eggs STH, b) minimize the danger of infection of worm eggs STH are: counselingbased public education through the internalization of Islamic values especially taharah , laboratory diagnosis,counseling and clinical manufacturing of the storage of manure (Temporary Shelter) as well as the simulationof the use of Personal Protective Equipment (PPE), c) the incidence of infection eggs STH on vegetablegrowers 0.017% of 60 farmers cabbage, d) stimulant research with the delivery of results manufacture thestorage of manure (Temporary Shelter) and the simulated use of PPE, e) internalization of Islamic valuestaharah an appropriate material in order to minimize the danger of infection with STH base in QS. Al Baqarah:222 and HR. Muslim.